Empowering Saudi women in leadership positions in the Ministry of Hajj and Umrah (1443 AH-2021 AD) - Abu Alshamat, Buthaina Adel; Asghar, Atif Hussain (Journal of Economic, Administrative and Legal Sciences, 2022)
Purpose - The purpose of this study is to assess the level of administrative empowerment of women and leadership positions in the Ministry of Hajj and Umrah, identify the most important challenges, and obstacles facing women working in leadership administrative positions. from the point of view of a sample of female employees and officials in the Ministry of Hajj and Umrah in the Kingdom of Saudi Arabia. Design/ Methodology/ Approach - To achieve the objectives of this study used the descriptive analytical method. The study population consisted of a number of female employees and officials in the Ministry of Hajj and Umrah, based on the intentional sampling method. Findings-The researcher reached the results show a high degree of concordance between the study vocabulary regarding the dimensions of empowerment in various jobs (74.18%), participation and qualification (72.06%), compared to the neutrality of consensus about the obstacles facing women’s empowerment in leadership positions (65.49%). With a varying level of agreement on the sub-items of those dimensions, which requires the need to establish the concept of women’s empowerment Administrative and leadership positions. In addition to the absence of statistically significant differences in the trends of the study vocabulary about the dimensions of administrative empowerment according to the educational level, social status and administrative experience. while there were statistically significant differences between the average estimates of the study sample members of the female employees to the degree of empowerment of Saudi women in leadership positions in the Ministry of Hajj and Umrah attributed for the functional status variable. The results also showed the obstacles to achieving women’s empowerment in administrative work and leadership positions. The study recommended working on upgrading the role of women in the work environment and believing in their ability to achieve success in the operational job roles that they perform, directing their characteristics and their view of advantages to be used in reaching leadership positions, attracting women leaders with experience to work in departments and branches, benefiting from Technical development and electronic communication and its adaptation to develop women’s work through remote work.